Regional Asset Information System Prototyping - Avin Wimar Budyastomo; Nia Agustina (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2025)
Abstract - Local asset management is one of the important aspects in efficient and transparent government administration. This research aims to develop a prototype information system that is able to support regional asset management in a more structured and integrated manner. The prototyping method is used in this research to enable rapid and flexible iteration during the system development process, as well as to accommodate dynamic user needs. The result of this research is a prototype of a regional asset information system that can facilitate the process of inventorying, monitoring, and reporting regional assets. The implementation of this prototype is expected to improve operational efficiency and data accuracy in regional asset management. Evaluation of the prototype was conducted by involving various stakeholders, including local asset managers and government officials, to ensure that the developed system meets practical needs in the field.Keywords : Regional Asset Management, Information System, Prototyping, Asset Inventory, Operational Efficiency Abstrak- Pengelolaan aset daerah merupakan salah satu aspek penting dalam administrasi pemerintahan yang efisien dan transparan. Penelitian ini bertujuan untuk mengembangkan prototipe sistem informasi yang mampu mendukung pengelolaan aset daerah secara lebih terstruktur dan terintegrasi. Metode prototyping digunakan dalam penelitian ini untuk memungkinkan iterasi yang cepat dan fleksibel selama proses pengembangan sistem, serta untuk mengakomodasi kebutuhan pengguna yang dinamis. Hasil penelitian ini adalah prototipe sistem informasi aset daerah yang dapat mempermudah proses inventarisasi, pemantauan, dan pelaporan aset daerah. Implementasi prototipe ini diharapkan dapat meningkatkan efisiensi operasional dan akurasi data dalam pengelolaan aset daerah. Evaluasi terhadap prototipe dilakukan dengan melibatkan berbagai pemangku kepentingan, termasuk pengelola aset daerah dan pejabat pemerintah, untuk memastikan bahwa sistem yang dikembangkan memenuhi kebutuhan praktis di lapangan.Kata kunci : Pengelolaan Aset Daerah,Sistem Informasi, Prototyping, Inventarisasi Aset, Efisiensi Operasional